2016
DOI: 10.36311/2674-8681.2016.v17n1.02.p9
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Future Physical Educators for Inclusion: Changing the Physical Education Teacher Training Program

Abstract: Students with disabilities around the world are leaving special schools and special classes and are receiving their education in general education schools. In addition to attending general education classes, these students with disabilities are attending general physical education classes. Unfortunately, research has clearly demonstrated that physical educators do not feel prepared to include students with disabilities into their general physical education classes. Such findings are not surprising given that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 0 publications
2
2
0
5
Order By: Relevance
“…For example, Carol stated, ‘I believe it’s very important to try and teach with an inclusive philosophy; however, I think it can be very difficult to do so’ (written reflection). This is consistent with a plethora of scholarly work that has indicated that in-service and preservice physical educators often feel unprepared to provide students with disabilities an inclusive PE experience (Block et al, 2016; Hutzler et al, 2019; Piletic and Davis, 2010). Participants also pointed out a number of barriers that would interfere with having an inclusive PE experience to students with disabilities, which included a lack of preparation, support, and strategies to promote inclusion.…”
Section: Resultssupporting
confidence: 76%
“…For example, Carol stated, ‘I believe it’s very important to try and teach with an inclusive philosophy; however, I think it can be very difficult to do so’ (written reflection). This is consistent with a plethora of scholarly work that has indicated that in-service and preservice physical educators often feel unprepared to provide students with disabilities an inclusive PE experience (Block et al, 2016; Hutzler et al, 2019; Piletic and Davis, 2010). Participants also pointed out a number of barriers that would interfere with having an inclusive PE experience to students with disabilities, which included a lack of preparation, support, and strategies to promote inclusion.…”
Section: Resultssupporting
confidence: 76%
“…For example, the infographic cards present a brief explanation of each para-sport, including information on the rules and the specific equipment needed for its practice, basic information about the classification system used in the para-sport, a brief biography of a local or national para-athlete and a QR code that directs the reader to a video that further explains each para-sport (e.g., Paralympics A-Z by the International Paralympic Committee). These types of materials encouraged interaction on the part of the PETs, and they could also be used in their regular PE classes as a training resource for their professional development [26]. The original version of the Incluye-T guide received minor adjustments for its implementation in the insular region, and it is available as Supplementary Material for this publication (appendix A).…”
Section: Discussionmentioning
confidence: 99%
“…Los modelos educativos vigentes buscan dar una respuesta a los desafíos de la sociedad actual, y en este sentido la normalización de personas con discapacidad es una prioridad en las sociedades avanzadas (Novo-Corti, Muñoz-Cantero & Calvo-Babío, 2015). En las aulas del siglo XXI se debe aceptar el reto de enseñar a una población estudiantil diversa, incluyendo aquellos con discapacidad (Hodge, Lieberman & Murata, 2017), ya que la inclusión de estos alumnos es claramente el futuro de educar a este colectivo (Block, Kwon & Healy, 2016) así como un derecho firmado por las Naciones Unidas (UNESCO, 2005). Este reto se refiere específicamente a la escuela inclusiva vinculada a una educación de calidad sin excepciones, y una filosofía que contempla la educación como motor de cambio social y de actitudes (Ríos, 2009).…”
Section: Actitudes Del Profesorado De Educación Física Hacia La Incluunclassified
“…Así las cosas, se observa que, en los últimos años, una parte vital para implementar una inclusión exitosa son las actitudes y la autoeficacia del docente (Reina, Ferriz & Roldán, 2019, Reina, Santana, Montesdeoca & Roldán, 2019. Comprender las perspectivas de los docentes sobre la inclusión es crucial en la investigación educativa (Abdi, 2017), más aún quizás el factor más importante para una inclusión exitosa en EF es la actitud y la competencia percibida de los docentes de EF (Block et al, 2016) porque las actitudes son un determinante importante del comportamiento de los docentes (Cyran, Kudlacek, Block, Malinowska-Lipien & Zyznawska, 2017).…”
Section: Actitudes Del Profesorado De Educación Física Hacia La Incluunclassified
See 1 more Smart Citation